Craniofacial Anthropometric Prole of Adult Ethnic (Santal) people of Northern Part of Bangladesh - Mondol, Henry Sandip Kumar; Ahmed, Wali; Mondol, Albert Sanjib (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: Cephalometry is one of the important parts of anthropometry which deals with the study of human head by analyzing various cephalometric points, planes, skeletal and soft tissue relationship of the face in order to determine morphological characteristics in human beings of various ethnic origin. The Santals are one of the major ethnic groups in Bangladesh. But no published data on their craniofacial anthropometrics have yet been found. The present study was designed to assess the normal craniofacial anthropometrics of the Santal population living in Rajshahi Division, the northern part of Bangladesh. Methods: This descriptive study was conducted for evaluation of craniofacial anthropometrical profile of adult Santals, an ethnic people of Northern part of Bangladesh, particularly in Rajshahi division. The study included a total of 70 Santals (35 males and 35 females ranging from 18-40 years of age) between July 2018 to June 2019. A lateral cephalograph was taken from each study subject and Steiner’s analysis was used for cephalometric measurements of the face. The data were collected on various angular measurements, such as SNA angle, SNB angle, ANB angle, UInc to NA angle, LInc to NB angle, interincisal angle, SN to Op angle, SN to GoGn angle (Fig.1). The different angular measurements derived from the Steiner’s analysis were then compared between males and females to find whether any of these angles were influenced by sex. Result: Majority (81.4%) of the study subjects was in their 3rd decade of life with median age of the subjects being 37.0±6.1 (range:18-40) years. SNA angle was approximately normally distributed; SNB was also almost normally distributed, for mean and median SNB were 78.8˚ and 79˚ respectively. The mean ANB angle was higher (2.64˚) than the median (2.0˚). The ANB angle was not assumed to follow a normal distribution curve. UInc to NA (˚) is also not normally distributed as the difference between mean (23.6˚) and median (25˚) is wide. Linc to NB (˚) assumed an almost normal distribution curve, for mean (35.4˚) and median (35˚) are narrowly different. Interincisal angle (˚) was also approximately normally distributed as indicated by narrow difference between mean (118.2˚) and median (119˚). The SN to Op angle (occlusal plane angle) tend to be left-sided skewness. SN to GoGn (mandibular plane angle) shows slight right-sided skewness with negligible difference between mean (33.2˚) and median (33.5˚). According to Steiner’s ‘S’ line 80% of the facial profile were of protrusive type and the rest 20% were of normal type. However, as different angular measurements were compared between sexes no significant difference was found between sexes. Conclusion: The Bangladeshi Santal population had a protrusive dento-alveolar structure. These differences should be kept in mind to facilitate better diagnosis, and orthodontic treatment for Bangladeshi patients. The results of the present study support the idea that a single standard of facial esthetics should not be applied to all racial and ethnic groups. Ibrahim Card Med J 2021; 11 (2): 69-76